Involvement of calmodulin in depolarization-induced release of corticotrophin-releasing hormone-41 from the rat hypothalamus in vitro. - Tsagarakis, S; Rees, L; Besser, G; Grossman, A (1991)
We have employed an acute explant system of the rat hypothalamus in vitro, as previously described, to examine the role of calcium and calmodulin in the release of corticotrophin-releasing hormone-41 (CRH-41). Release of CRH-41, as determined by radioimmunoassay, was stimulated in a dose-dependent manner by the membrane-depolarizing agents KCl and veratridine. Stimulation was also observed with the calcium ionophore A23187. The calcium channel blocker verapamil (1-100 mumol/l) inhibited both KCl- and veratridine-induced release in a dose-dependent manner (maximum inhibition of 75% and 60% respectively), thus providing further evidence that calcium entry is required for secretion of CRH-41 following membrane depolarization. Trifluoperazine (1-100 mumol/l), an inhibitor of calmodulin-calcium interaction, decreased both KCl- and veratridine-evoked CRH-41 secretion in a dose-dependent fashion (maximum inhibition of 50% and 30% respectively). Similarly, phenytoin, a calmodulin-dependent kinase inhibitor, in the concentration range of 1-100 mumol/l, also decreased depolarization-induced CRH-41 release in a dose-dependent manner. The basal release of CRH-41 was unaffected by either treatment. Finally, both calmodulin inhibitors (10 mumol/l) decreased CRH-41 release induced by the calcium ionophore A23187 (10 mumol/l). These data provide evidence for the role of calcium in membrane depolarization-induced stimulus-secretion coupling of rat hypothalamic CRH-41. Furthermore, inhibition of the stimulatory responses by two separate classes of calmodulin inhibitors suggests a role for calmodulin, at least in part, in this process.